Identifying Sustainable Development Goals (SDG's) on the Papua-Papua New Guinea Skouw Border as Study Material for the Development of the ASEAN Outlook on Indo-Pacific Framework: A case study in Skouw Mabo Village, Muara Tami District, Jayapura City - Pugu, Melyana Ratana (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This study aims to obtain an in-depth analysis of the implementation of development based on sustainable development goals on the border of Papua and Papua New Guinea, especially in the border village of Skouw Mabo, Muara Tami District, Jayapura City. that countries in the world today continue to strive to create a state of every society that lives sustainably because there are various indicators offered to achieve sustainable life known as the concept of sustainable development goals (SDG's). The SDG's is a sustainable development program prepared by UN member countries in 2015 and is expected to be achieved by 2030. This border research uses a qualitative research method, namely by collecting data directly through observation and interviews, then the data is processed by filtering various data and information obtained to then be presented in the form of an in-depth analysis of the implementation of sustainable development in the border village of Skouw Mabo. The results of the study show that the components of SDG's indicator 4 are quality education, indicator 5 is gender equality; Indicator 6 is clean water and proper sanitation and indicator 10 of the SDG's is the reduction of the gap that has not been seen in the border village of Skouw Mabo which is described quite clearly in this paper. The role of the local government, districts, cities and also community elements as well as private parties and non-governmental organizations are very necessary for the sustainability of development in this region.